PENGARUH STRATEGI PEMBELAJARAN AFEKTIF TERHADAP SIKAP SOSIAL SISWA PADA MATA PELAJARAN AKIDAH AKHLAK KELAS VIII DI MTSN 1 KUANTAN SINGINGI (TP.2021/2022) - Winda Puspita Dilla; Andrizal Andrizal; Zulhaini Zulhaini (Universitas Islam Kuantan Singingi, 2023)
This research is motivated by an Affective learning strategy which has the main goal of being able to make decisions based on values ​​that are considered good. In fact, students still lack social attitudes. Social attitude is an individual's tendency to take an action. The response that occurs in attitude is a consistent response. Attitude is reflected in the behavior or actions of each individual. If a person behaves well, it can be said that his attitude is good. Social Attitudes of Students in the Subject of Aqidah Akhlak Class VIII at MTSN 1 Kuantan Singingi (TP.2021/2022). This research is a causal associative research, which was conducted at MTSN 1 Kuantan Singingi. The data collection technique used was a questionnaire with instruments in the form of questionnaires, interviews, observation and documentation. Data analysis used the SPSS for Window Release 21.0 program. The results showed that there was a positive and significant effect of the affective learning strategy on the significance test found the equation that the value (sig.) 0.03 < than the probability of 0.05 so it was concluded that there was an effect of variable X on Y.